Farmer research and extension - Knox, Anna; Lilja, Nina (International Food Policy Research Institute, 2004)
In this brief, we learn that combining technical innovations with collective action initiatives has been shown to lead to substantial farmer benefits. A number of farmer-led research and extension (FRE) approaches incorporate collective action for different purposes and at different stages in the innovation process. Collective action can be useful in sharing knowledge, setting priorities, and experimenting with, evaluating, and disseminating technologies. The authors describe various participatory research approaches such as farmer field schools (FFSs), local agriculture research committees (CIALs), farmer research groups (FRGs), and farmer innovation approaches (FIAs) -- from Text.